STRATEGI PEMERINTAH DALAM MENANGANI TINDAK KEKERASAN TERHADAP PEREMPUAN DI KOTA KENDARI - Rasmin (Halu Oleo University, 2024)
The research aims to describe and analyze the government’s strategy in dealing with victims of violence against women in the city of Kendari. This type of research uses a qualitative descriptive approach, determining informants using purposive sampling with 4 informants. Data collection in this study was done through interviews, observation, and documentation studies. Data analysis includes data reduction, data presentation, conclusion, and verification. The results of this study indicate that the background of violence against women is dominated by patriarchal culture and economic dependence. While the government’s strategy in dealing with victims of acts of violence against women is carried out by minimum service standards for women’s protection, however, spiritual guidance services have not been implemented at the women’s and empowerment agency and child protection in Kendari city.